Profil Keterampilan Kerjasama Siswa Kelas VII di Salah Satu SMP Swasta di Magelang - Mayasari Mahfudhotul Khasanah; Adhe Bayu Pangestu; Intantiasari Intantiasari; Noni Shella HP; Fitri Susanti; Baskoro Adi Prayitno (Jurnal Pendidikan Biologi, 2018)
This study aims to determine the profile of cooperation skills of grade VII students in one private junior high school in Magelang. This study uses a survey method. The study population was all seventh grade junior high school students. The sampling technique uses purposive random sampling with a sample of 25 students. Students' cooperative skills are measured in classroom observations, questionnaires, and interviews. Data analysis used qualitative descriptive analysis. The results of this study indicate that of 36 students there are 0% of students who have very low collaboration skills, 0% of students who have low cooperative skills, 0% of students who have moderate cooperation skills, 72% of students who have high cooperative skills, and 28% of students who have very high cooperation skills. The average cooperative skills of class VII students are high.